Health Literacy and Early Detection Skills of Dengue Hemorrhagic Fever in Adolescents - Putra, Ilham Syarochman; Hartinah, Dewi; Jauhar, Muhamad (Jurnal Keperawatan Priority, 2025)
Dengue hemorrhagic fever (DHF) is a significant public health problem in Indonesia, especially in tropical areas such as Jepara Regency. The increase in DHF cases in adolescents is caused by low health literacy and a lack of confidence in early detection skills that play an important role in preventing DHF. The impact is the occurrence of complications to the economic impact of the community in the treatment phase. This study aims to analyze the relationship between health literacy with early detection skills for DHF in adolescents. This study aims to analyze the relationship between health literacy and health beliefs with early detection skills of DHF in adolescent groups at SMAN 1 Tahunan, Jepara Regency. This study used a correlational analytical design with a cross-sectional approach. Independent variables are health literacy Dependent variables are early detection skills of DHF. This study was conducted in November at SMAN 1 Tahunan, the number of samples was 93 students selected using purposive sampling techniques. The research instrument used health literacy instruments (HLS-12Q),), and early detection behavioral skills of DHF. Data analysis was carried out using the chi-square test. The results of the study showed that there was a significant relationship between health literacy and early detection skills of DHF with a p-value = 0.000, health literacy is related to early detection skills. With this, schools and health centers can collaborate in improve health literacy, skills and early detection of DHF.